The knowledge regions in the enlarged Europe - Marta Foddi; Raffaele Paci; Alessandra Colombelli (European Regional Science Association (ERSA), 2011)
Since the Lisbon agenda in 2000, Europe stated the goal to become the most advanced knowledge economy in the world relying specifically on the increase and strengthen of its human capital and technological endowments. However, given the presence of localized externalities in the knowledge accumulation process, this policy may produce distortive and unwanted consequences at the territorial level reinforcing the existing high inequalities among regions. Another crucial feature to be considered is the recent enlargement process of the European Union which has brought on stage new players characterized by a low average level of knowledge activity accompanied by a huge degree of internal territorial disparity. The aim of this paper is to identify the "knowledge regions" in Europe and to examine their main territorial features. To this aim we first build, for 287 regions belonging to 31 European countries, a comprehensive picture of the two variables - human capital and technological activity - which constitute the main pillars of the knowledge economy. For each of these two variables we construct several indicators examining their spatial distribution across the European regions. Further, we compute two synthetic indicators for human capital and technology and, on the basis of these two dimensions, we finally identify the knowledge regions.
Keywords: 330